Servingness in the Borderlands: A Study of Faculty Hiring at a Hispanic-Serving Institution on the Border - Cynthia D. Villarreal (SAGE Publishing, 2022)
This evaluation of faculty hiring examines how eight faculty search chairs at a border Hispanic-serving institution (HSI) discuss how they enact an HSI consciousness when making hiring decisions. Using a combined phenomenological case study approach, the author examines hiring through a conceptual framework that brings together organizational culture and Borderlands theory to understand how committee decisions on hiring are informed by their campus's HSI designation and cultural identity. Through analysis of faculty search chair interviews, faculty search chairs at a borderland HSI are committed to hiring with their student population in mind by enacting a Latinx-serving consciousness. Overall, the findings of this study contribute to a broader conversation on servingness as well as scholarship on how educators and administrators can embrace the cultural values that their Latinx students possess to make decisions in hiring.